STUDY ON THE EFFECTIVENESS OF ADDING SOME PLANT EXTRACTS WITH BHT ON MEAT QUALITY OF LAMB PATTIES DURING CHILLING STORAGE - Ibrahim, A. Baker (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was aimed to evaluate and compare the effects of adding natural extracts (clove, Mentha and thyme) with synthetic BHT on some physiochemical, microbial, and sensory characteristics of lamb patties stored at 4 Cº for 12 days. Results indicated that there’s a steady rise (P